Grenadian cats as potential reservoir for Leptospira. - Keith K Kalasi; Daniel Fitzpatrick; Diana Stone; Talia Guttin; Andy Alhassan (PLoS Neglected Tropical Diseases)
Leptospirosis is a spirochetal disease caused by Leptospira spp. bacteria with global distribution affecting multiple mammalian species, including humans. The disease is endemic in many geographic areas and is of particular concern in tropical regions with abundant rainfall, such as the Caribbean. Currently, there are no published reports on Leptospira exposure or infection in Grenadian cat populations, and the role of cats in the epidemiology of the disease is unknown. Our hypothesis is that Grenadian cat population may be a reservoir host for zoonotic Leptospira on the island. During 2019-2021, 160 feral cats were captured from three parishes in Grenada, and their urine and blood were tested for Leptospira. Urine from 4 of 148 (2.7%) cat samples tested PCR-positive for Leptospira. Serum from 6 of 136 (4.4%) cat samples tested PCR-positive for Leptospira. Sequence analysis of the Leptospira rpoB gene showed 86-100% similarity to known or presumed pathogenic Leptospira species. The findings of this study suggest that Grenadian cat populations are infected with and are shedding Leptospira genotypes that are phylogenetically related to known pathogenic Leptospira, including known zoonotic strains. These observations support the hypothesis that Grenadian cat populations may be a reservoir host for zoonotic Leptospira on the Island.